2006
DOI: 10.1623/hysj.51.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Incertitude d'estimation des pluies extrêmes du pourtour méditerranéen: illustration par les données de Marseille

Abstract: Résumé Le modèle de renouvellement-dépassement est un modèle statistique fréquemment utilisé en hydrologie pour l'estimation de quantiles extrêmes. D'un point de vue théorique, cette modélisation stipule que les dépassements d'un seuil suffisamment élevé se distribuent, sous des hypothèses générales d'indépendance et d'homogénéité, selon une famille de lois paramétriques dites lois de Pareto généralisées, pour laquelle la loi exponentielle est un cas particulier. En pratique, très souvent, la loi exponentielle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…[21] concludes in France that Gumbel's law does not predominate in the estimation of extreme rainfall. These results confirm some author's skepticism as to this law exclusive use in the extreme rain estimation in engineering [22], [23] and [24]. However, [25] emphasizes that Gumbel's law using amounts to giving maximum risk to engineering works by underestimating the quantiles.…”
Section: Discussionsupporting
confidence: 82%
“…[21] concludes in France that Gumbel's law does not predominate in the estimation of extreme rainfall. These results confirm some author's skepticism as to this law exclusive use in the extreme rain estimation in engineering [22], [23] and [24]. However, [25] emphasizes that Gumbel's law using amounts to giving maximum risk to engineering works by underestimating the quantiles.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Koutsoyiannis and Baloutsos (2000), Chaouche et al (2002), , , Sisson et al (2006), Koutsoyiannis (2004a, b) and Bacro and Chaouche (2006) have shown that extreme rainfall quantiles can be seriously underestimated by the Gumbel distribution. This discussion has significant practical consequences, particularly for high return periods used for the design of major hydraulic constructions or the estimation of risk of extreme floods.…”
Section: Distribution Of Annual Maximum Rainfallmentioning
confidence: 99%
“…The natural climate variability in the Mediterranean basin and the Middle East is very high (Xoplaki et al, 2004;Lionello et al, 2006;López-Moreno et al, 2007) and related uncertainties are significant (Bacro & Chaouche, 2006;Koutsoyiannis & Montanari, 2007). To date, no uniform regional pattern has been identified across the Mediterranean region.…”
Section: Climate Changementioning
confidence: 99%